Culture, Cognition, and Emotion in China's Religious Ethnic Minorities: Voices of Suffering among the Yi - Chen, Xinjie (Palgrave Studies in Indigenous Psychology, 2017)
"Foreword" -- "Preface" -- "Contents" -- "List of Figures" -- "List of Tables" -- "Chapter 1: First Things First: Research Orientation andÂ Background Information onÂ Two Yi Communities inÂ Southwest China" -- "Scope ofÂ Our Study: AnÂ Unusual Blend ofÂ Approaches" -- "Theoretical Framework" -- "Aim ofÂ Our Study: What Is This Study About?" -- "The Historical Background ofÂ Yi andÂ theÂ Native Bimo Tradition" -- "The Introduction ofÂ Christianity inÂ Southwestern China" -- "Research Sites inÂ Yunnan andÂ Sichuan" -- "Meigu Town (ç¾å)" -- " Bimo Religious Tradition" -- "Luquan Town (ç¦å)" -- "Culture andÂ Cognition: Theoretical Predictions" -- "Research Methodology" -- "First Phase" -- "Second Phase" -- " Interview Protocol" -- " Data Analysis" -- "Third Phase: Validity Check andÂ Case Study" -- "Structure ofÂ This Book" -- "References" -- "English Titles" -- "Chinese Titles" -- "Online Resources" -- "Chapter 2: Narratives ofÂ Suffering" -- "Self-Reflection ofÂ theÂ First Author: AÂ Pilgrimage toÂ Indigenous Psychology" -- "Narratives ofÂ Suffering fromÂ Yi-Bimo" -- "Story ofÂ EM (Narrated by Xiaorong)" -- "Story ofÂ SZ (Narrated by Keke)" -- "Story ofÂ LQ (Narrated by Xiaorong)" -- "Thematic Analysis: Yi-Bimo Group" -- " Theme 1. Financial Difficulties -- Theme 12. Climate Problems" -- "Theme 2. Family Membersâ Illness andÂ Death" -- "Theme 3. Personal Medical Conditions -- Theme 5. Physical Pains andÂ Discomfort" -- "Theme 4. Family Problems andÂ Burdens -- Theme 9. Substance Addiction inÂ theÂ Family -- Theme 10. Pressures inÂ Family Lineage" -- "Theme 6. Lack ofÂ Social Support -- Theme 11. Conflicts withÂ Authority" -- " Theme 7. Psychological Turmoil -- Theme 8. Suicides" -- "Narratives ofÂ Suffering ofÂ Yi-Christians" -- "Story ofÂ Grandpa SC (Narrated by Zhangying)" -- "Story ofÂ Grandma W (Narrated by Xinli)